Freedom through exile. - Kwa, Brennan Yiew Khoon. (2010)
Le Clézio was awarded the Nobel Prize in Literature in 2008, prior to the Nobel Prize, most of the English literary world did not even know of Le Clézio (due mostly to a dearth of English translations of his literary works). It is therefore a matter of not only interest but importance to provide English scholarship of Le Clézio’s works. To that end, this essay will attempt to analyze Le Clézio’s constant concern with exile that he continually examines within his literature. By applying Edward Said’s theories and work on exile studies, Le Clézio’s purposes and objectives behind his use of the theme of exile can thus be revealed. By studying and looking at Le Clézio’s The Interrogation, The Flood and Desert, one will thus be able to determine Le Clézio’s shift from a radically experimental modernistic writing style in his earlier works to a more subtle and postcolonial take in his later works. Though his writing style has changed dramatically, Le Clézio however remains committed to the mission of using his literature to help his readers attain freedom through exile.